1961
DOI: 10.1021/j100823a006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Added Hexachloroethane on the Radiolyses of Carbon Tetrachloride and Chloroform

Abstract: HC1 yields from irradiated chloroform are, for doses a t least as high as 1.3 X 1021 e.v. per gram, greater a t 70 i 4" than at 20". The initial G-value at the higher temperature is 31 compared wit! an average of 11.9 at 20'. Chlorine yields from irradiated carbon tetrachloride are slightly smaller a t i 0 f 4" than at 20 . The corresponding G-values are 0.58 and 0.65.The addition of hexachloroethane to carbon tetrachloride prior to irradiation causes a nearly linear decrease in G(cin) with per cent. hexachlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1963
1963
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A large number of reports have previously focused on chloroform radiolysis in various contexts and experimental conditions (Abadie, 1982;Bibler and Hyder, 1968;Chen et al, 1960;Johnston et al, 1961;Ottolenghi and Stein, 1961;Schulte et al, 1953;Werner and Firestone, 1965). These authors suggested that hydrogen chloride is the main product of chloroform radiolytic degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of reports have previously focused on chloroform radiolysis in various contexts and experimental conditions (Abadie, 1982;Bibler and Hyder, 1968;Chen et al, 1960;Johnston et al, 1961;Ottolenghi and Stein, 1961;Schulte et al, 1953;Werner and Firestone, 1965). These authors suggested that hydrogen chloride is the main product of chloroform radiolytic degradation.…”
Section: Introductionmentioning
confidence: 99%
“…However, all these publications (from the 50's to the 80's) gave equivocal radiolytic yield (G-yield) of generated hydrogen chloride because of differences in the experimental conditions. Either chloroform solutions purity were different which implies discrepancies in G-yield of HCl (Abadie, 1982;Chen et al, 1960;Johnston et al, 1961;Ottolenghi and Stein, 1961) or experimental conditions, for example various temperature, pressure or radiation dose rate (Bibler and Hyder, 1968;Johnston et al, 1961;Schulte et al, 1953;Werner and Firestone, 1965). For these reasons, we planned to revisit the experimental measurements of HCl yield during γ-ray experiments, more easy to be measured and close to the α ones, in specifically well-defined conditions in order to establish the potential quantities of HCl in routine production of astatine-211 solution during radiolabeling and production of [ 211 At]-astatinated radiopharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%